Radiation shielding of protoplanetary discs in young star-forming regions - Wilhelm, Martijn J. C.; Portegies Zwart, Simon; Cournoyer-Cloutier, Claude; Lewis, Sean C; Polak, Brooke; Tran, Aaron; Mac Low, Mordecai-Mark (Monthly notices of the Royal Astronomical Society, 2023)
Protoplanetary discs spend their lives in the dense environment of a star-forming region. While there, they can be affected by nearby stars through external photoevaporation and dynamic truncations. We present simulations that use the amuse framework to couple the torch model for star cluster formation from a molecular cloud with a model for the evolution of protoplanetary discs under these two environmental processes. We compare simulations with and without extinction of photoevaporation-driving radiation. We find that the majority of discs in our simulations are considerably shielded from photoevaporation-driving radiation for at least 0.5 Myr after the formation of the first massive stars. Radiation shielding increases disc lifetimes by an order of magnitude and can let a disc retain more solid material for planet formation. The reduction in external photoevaporation leaves discs larger and more easily dynamically truncated, although external photoevaporation remains the dominant mass-loss process. Finally, we find that the correlation between disc mass and projected distance to the most massive nearby star (often interpreted as a sign of external photoevaporation) can be erased by the presence of less massive stars that dominate their local radiation field. Overall, we find that the presence and dynamics of gas in embedded clusters with massive stars is important for the evolution of protoplanetary discs.
Gesehen am 24.11.2023